Appropriate use of laboratory test requests in the emergency department: a multilevel intervention. (June 2019) - Nazerian, Peiman; Vanni, Simone; Fanelli, Alessandra; Fallai, Linda; Duranti, Cesare; Ognibene, Agostino; Rapi, Stefano; Betti, Laura; Tomaiuolo, Matteo; Calamai, Monica; Grifoni, Stefano
Abstract : Objective: Laboratory test requests in the emergency department (ED) are increasing worldwide. We evaluated whether a multilevel intervention on the basis of the optimization of test profiles and educational meetings with physicians could reduce the number of tests ordered. Patients and methods: In a single-center before and after study design, the 8-month intervention period was compared with the 8-month preintervention period. Laboratory test profiles were reduced from 6 to 2 and the number of tests in each profile was reduced by 50%. All physicians received education about the costs and appropriate use of the tests. Primary outcomes were the number of laboratory blood tests and their costs, with a focus on high-cost tests. Secondary outcomes were ED and laboratory performances (patients' waiting time, number of deaths in ED, re-entry, laboratory turn-around time, and add-on tests). Results: Overall, 61 976 and 61 154 patients were evaluated, respectively, during the intervention and the preintervention period. Laboratory blood test requests were decreased by 207 637 (−36.3%) in the intervention period ( P < 0.05), which corresponds to a reduction of 337.3 tests/100 patients. Costs were decreased by 608 079[Euro sign] ( − 29.6%, P < 0.05), leading to a cost reduction of 981.2[Euro sign]/100 patients. High-cost test requests decreased by 11 457 ( − 27.3%) and contributed toward the overall reduction in costs with 197 206[Euro sign] ( − 30.5%). No significant differences were found in ED and laboratory performances between intervention and preintervention periods. Conclusions: Optimization of test profiles and education on the costs and appropriate use of the tests significantly reduced laboratory test ordering and costs without affecting ED and laboratory performances.